Evaluation of the genotoxicity of gold nanoparticles by single-cell electrophoresis - de la Cruz-Barrios, Juan D.; Abrica-González, Paulina; Gutiérrez-Cruz, Sinai G.; Muñoz-Diosdado, Alejandro; Mendoza Pérez, Jorge A.; Sánchez-González, Armando Y. (Frontiers in Nanotechnology, 2025)
The distinctive characteristics and wide-ranging applications of gold nanoparticles (AuNPs) have sparked considerable scientific interest, leading to increased use and a rise in publications and patents. However, their environmental and genotoxic impact remains poorly understood. In this study, we evaluated the genotoxicity and mutagenicity of AuNPs in germinated roots of Vicia faba using three approaches: a comet assay to detect DNA damage, mitotic index analysis, and assessment of chromosomal abnormalities. We observed a reduced mitotic index, increased chromosomal abnormalities, and significant DNA damage in treated samples, indicating genetic alterations and a potential environmental risk. These findings underscore the significance of evaluating the biological effects of AuNPs and demonstrate that single-cell electrophoresis is a reliable tool for assessing genetic damage in plants.